4x=-2x-42

Simple and best practice solution for 4x=-2x-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x=-2x-42 equation:


Simplifying
4x = -2x + -42

Reorder the terms:
4x = -42 + -2x

Solving
4x = -42 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
4x + 2x = -42 + -2x + 2x

Combine like terms: 4x + 2x = 6x
6x = -42 + -2x + 2x

Combine like terms: -2x + 2x = 0
6x = -42 + 0
6x = -42

Divide each side by '6'.
x = -7

Simplifying
x = -7

See similar equations:

| 3x+2.5=4x-35 | | 4(2-2y)+6=2(7+4y) | | 18x-3y=6 | | 2+2m=4m+5 | | -3x+3/5+1/5=2(4-x)/5 | | -13-(3m+4)= | | (1-u)(2u-7)=0 | | x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 | | 5x^2+18x-8=0 | | 2.5x+15+0.5(x-4)=1.2x+2(0.5x-6) | | 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 | | 3(4x-3)+2x=89 | | .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 |

Equations solver categories